THE CORRECT NAME FOR THE TETRASTIGMA (VITACEAE) HOST OF RAFFLESIA (RAFFLESIACEAE) IN MALESIA AND A (NOT SO) NEW SPECIES - Jan Frits Veldkamp (BRIN Publishing (Penerbit BRIN), 2008)
VELDKAMP, J.F. 2008. The correct name for the Tetrastigma (Vitaceae) host of Rafflesia (Rafflesiaceae) in Malesiaand a (not so) new species. Reinwardtia 12(4): 261 – 265. ––The correct name for Tetrastigma lanceolarium auct.non Planch. or T. leucostaphylum (Dennst.) Alston ex Mabb. (Vitaceae) in Malesia is T. rafflesiae Miq. The name T.lawsonii is superfluous and has been misapplied to a species here described as new.